Income Tax Of Individuals In Peru - Amat y León, Carlos (1980)
Economic theory has to conceptualize the "economic reality" as a process. More precisely, as a system that operates through the interaction of social groups through their respective economic agents. These agents have different behaviors and have unequal terms of trade. "Reality" is the continuing transformation of these phenomena under the conflict of opposing interests, but also the dynamism of common interests. To understand the economic phenomenon, predict events and change the course of history is important to analyze in depth the power structure of society, to study the actual behavior of economic agents as part of social groups that you understand and establish joint between them. Thus can be explained, ultimately, changes in levels and rates with changing economic events. This is the case, for example, taxes, government spending, personal income, production, utilities, among others. The terms of trade - the matrix of prices, wages, interest rates, exchange rates, profit - expressed on the other hand, the correlation of forces between social groups in the system.